Potential of rejected sago starch as a coating material for urea encapsulation - Rajan, Kavitha; Omar, Latifah; Ahmed, Osumanu Haruna; Charles, Primus Walter; Kasim, Susilawati (Multidisciplinary Digital Publishing Institute, 2023)
Increases in food production to meet global food requirements lead to an increase in the demand for nitrogen (N) fertilizers, especially urea, for soil productivity, crop yield, and food security improvement. To achieve a high yield of food crops, the excessive use of urea has resulted in low urea-N use efficiency and environmental pollution. One promising alternative to increase urea-N use efficiency, improve soil N availability, and lessen the potential environmental effects of the excessive use of urea is to encapsulate urea granules with appropriate coating materials to synchronize the N release with crop assimilation. Chemical additives, such as sulfur-based coatings, mineral-based coatings, and several polymers with different action principles, have been explored and used for coating the urea granule. However, their high material cost, limited resources, and adverse effects on the soil ecosystem limit the widespread application of urea coated with these materials. This paper documents a review of issues related to the materials used for urea coating and the potential of natural polymers, such as rejected sago starch, as a coating material for urea encapsulation. The aim of the review is to unravel an understanding of the potential of rejected sago starch as a coating material for the slow release of N from urea. Rejected sago starch from sago flour processing is a natural polymer that could be used to coat urea because the starch enables a gradual, water-driven mechanism of N release from the urea–polymer interface to the polymer–soil interface. The advantages of rejected sago starch for urea encapsulation over other polymers are that rejected sago starch is one of the most abundant polysaccharide polymers, the cheapest biopolymer, and is fully biodegradable, renewable, and environmentally friendly. This review provides information on the potential of rejected sago starch as a coating material, the advantages of using rejected sago starch as coating material over other polymer materials, a simple coating method, and the mechanisms of N release from urea coated with rejected sago starch.